2023
DOI: 10.1186/s12887-023-03839-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of obesity and high blood pressure among school-age children from military families: the largest report from our region

Abstract: Background For the first time, we aimed to determine the epidemiology and associated factors of obesity and hypertension among children of military families in our region. Methods In this multi-centered study, children between the ages of 5 to 12 years old, entered the study. Data on baseline and clinical characteristics, history of disease and anthropometric measurements, were collected. Results Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Dormanesh et al found a family history-related elevation in risk of hypertension above and beyond the contribution of BMI. 59 The association re ects a genetic propensity of hypertension, as well as non-genetic factors, such as shared lifestyle. 56,60 Our ndings showing strong associations between the mothers with obesity phenotype and incident hypertension are consistent with those of Dormanesh and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Dormanesh et al found a family history-related elevation in risk of hypertension above and beyond the contribution of BMI. 59 The association re ects a genetic propensity of hypertension, as well as non-genetic factors, such as shared lifestyle. 56,60 Our ndings showing strong associations between the mothers with obesity phenotype and incident hypertension are consistent with those of Dormanesh and colleagues.…”
Section: Discussionmentioning
confidence: 99%